High field metabolic rates of wild harbour porpoises - Rojano-Doñate, Laia; McDonald, Birgitte I.; Wisniewska, Danuta M.; Johnson, Mark; Teilmann, Jonas; Wahlberg, Magnus; Højer-Kristensen, Jakob; Madsen, Peter T. (Journal of Experimental Biology, 2018)
Reliable estimates of field metabolic rates (FMRs) in wild animals are essential for quantifying their ecological roles, as well as for evaluating fitness consequences of anthropogenic disturbances. Yet, standard methods for measuring FMR are difficult to use on free-ranging cetaceans whose FMR may deviate substantially from scaling predictions using terrestrial mammals. Harbour porpoises ( Phocoena phocoena ) are among the smallest marine mammals, and yet they live in cold, high-latitude waters where their high surface-to-volume ratio suggests high FMRs to stay warm. However, published FMR estimates of harbour porpoises are contradictory, with some studies claiming high FMRs and others concluding that the energetic requirements of porpoises resemble those of similar-sized terrestrial mammals. Here, we address this controversy using data from a combination of captive and wild porpoises to estimate the FMR of wild porpoises. We show that FMRs of harbour porpoises are up to two times greater than for similar-sized terrestrial mammals, supporting the hypothesis that small, carnivorous marine mammals in cold water have elevated FMRs. Despite the potential cost of thermoregulation in colder water, harbour porpoise FMRs are stable over seasonally changing water temperatures. Varying heat loss seems to be managed via cyclical fluctuations in energy intake, which serve to build up a blubber layer that largely offsets the extra costs of thermoregulation during winter. Such high FMRs are consistent with the recently reported high feeding rates of wild porpoises and highlight concerns about the potential impact of human activities on individual fitness and population dynamics.